2003
DOI: 10.4141/s01-063
|View full text |Cite
|
Sign up to set email alerts
|

Acari and Collembola biodiversity in Canadian agricultural soils

Abstract: Behan-Pelletier, V. M. 2003. Acari and Collembola biodiversity in Canadian agricultural soils. Can. J. Soil Sci. 83: 279-288. In Canadian agricultural soils, mites (Acari) are the most diverse and abundant arthropods. In comparison with other arachnids, mites are notable for their small size, diverse feeding habits, often complex life histories, and the range of habitats in which they live. Collembola are also abundant and diverse in soil and litter, they are in the same size range as the Acari, and for that r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(43 citation statements)
references
References 73 publications
3
38
0
1
Order By: Relevance
“…The findings suggest that predators are less sensitive than arthropods belonging to other trophic levels to the scarce organic matter content and to agricultural practices (Turbe´et al 2010). This is in agreement with Behan-Pelletier (2003) that report that agricultural practices can modify the structure of Acarina community, reducing species more susceptible to damages, such as Oribatida, and encouraging the multiplication of predator species, such as Gamasida. Anyway, the recent scientific literature re-ports controversial results about the factors that can drive the abundance of predators in soils.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The findings suggest that predators are less sensitive than arthropods belonging to other trophic levels to the scarce organic matter content and to agricultural practices (Turbe´et al 2010). This is in agreement with Behan-Pelletier (2003) that report that agricultural practices can modify the structure of Acarina community, reducing species more susceptible to damages, such as Oribatida, and encouraging the multiplication of predator species, such as Gamasida. Anyway, the recent scientific literature re-ports controversial results about the factors that can drive the abundance of predators in soils.…”
Section: Discussionsupporting
confidence: 93%
“…In fact, a decrease of their diversity and abundance has been highlighted in high-polluted soils (McIntyre et al 2001;Eitminaviciute 2006;Gongalsky et al 2010), whereas an increase was observed in urban soils with high organic matter content (Goddard et al 2009;Santorufo et al 2015). Instead, agriculture has been found to affect soil biological diversity at different levels within the soil food web, ranging from the microbial community to arthropods (Wardle 1995;Yeates et al 1997;Behan-Pelletier 2003;Postma-Blaauw et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Large numbers of microarthropods are found in most soils [36,37] (Table 1), including those under cultivation [38,39], and these animals may be the dominant arthropods in a variety of environments from equatorial to polar regions and from temperate and tropical forests and grasslands to hot and cold deserts [34,[40][41][42][43]. As part of the mesofauna, the microarthropods comprise the important middle links of soil food webs, serving, in their role as both predator and prey, to channel energy from the soil microflora and microfauna to the macrofauna on higher trophic levels [5].…”
Section: Microarthropodsmentioning
confidence: 99%
“…4.1 ), of the order Mesostigmata, is one of the most abundant and diverse groups of predatory mites living in excrements or decomposing animals (Vitzthum 1930 ;Koehler 1999 ;Behan-Pelletier 2003 ;Gerson et al 2003 ;Braig and Perotti 2009 ;Lindquist et al 2009 ;Perotti and Braig 2009 ). Filipponi ( 1964 ) divided the macrochelids into three main groups, fi micolous, humicolous and insecticolous, referring to their association with excrements, humus or insects (mainly as carriers of these mites).…”
Section: Introductionmentioning
confidence: 99%